Detection of aggressive periodontitis by calprotectin expression - Desi Sandra Sari; Suryono Suryono (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Calprotectin is a calcium-binding protein expressed by neutrophil, monocytes, gingival keratinocytes, and oral epithelial cells. The concentrations of calprotectin increase in plasma, urine and synovial fluid of patients with inflammatory diseases. This protein is known as a marker for periodontal diseases and is detected in gingival crevicular fluids. Purpose: This study was aimed to investigate the detection of inflammation on the aggressive periodontitis by calprotectin expression. Method: The gingival crevicular fluids were taken from five aggressive periodontitis patients and five healthy subjects by using sterile paper points. Calprotectin expression was analyzed by ELISA technique. Result: The results showed the significant difference in calprotectin expression between subject with aggressive periodontitis and healthy subjects p = 0.002 (p < 0.05). Conclusion: It was concluded that the calprotectin expression on the aggressive periodontitis patients may be useful for evaluation the progression of inflammation in periodontitis.